Religion at Carthage 800 BCE-439 CE: from Baal-Hammon to Christ - Merdinger, J. E.; Hoover, Jesse A.; Weatherwax, Nancy (Vigiliae Christianae. Supplements, 2025)
"This volume investigates the rich spectrum of religious practices and beliefs at Carthage from its foundation until the end of Roman rule. Essays analyse the metropolis's Phoenician, Punic, and Graeco-Roman cults (all exhibiting a remarkable degree of assimilation and amalgamation), mystery cults, Judaism, and Manichaeism. A majority of essays comprehensively examine Christianity's development (including persecution, martyrdom, Montanism, and Donatism) within Carthage's multi-cultural environment. Utilizing methodologies from popular culture studies, biblical exegesis, cultural studies, and archaeology, contributors cover such innovative topics as: polytheistic religiosity; Jewish identity and devotional life based on a recently discovered ancient synagogue near Carthage; and challenges experienced by St. Augustine as a guest-preacher to rambunctious congregations at Carthage"-- Provided by publisher
Keywords: Carthage (Extinct city); Church history; Religion